Re‐establishing the mid‐storey tree Persoonia longifolia (Proteaceae) in restored forest following bauxite mining in southern Western Australia. Issue 5 (7th June 2016) - Chia, Kerryn A.; Koch, John M.; Sadler, Rohan; Turner, Shane R.
Abstract: Persoonia longifolia is a common mid‐storey species that is difficult to return to post‐mining environments. This study aimed to quantify in situ emergence of P. longifolia seeds on restored areas, investigate seed cueing prior to use in restoration and assess different tree guards for increasing seedling survival and health. Initial investigations found that <1 % of seeds buried or scattered on restored areas produced seedlings. However, if seeds were cued through burial in surrounding forest, retrieved and sown on restored areas, seedling emergence increased to 24 %. Significantly more seeds emerged as seedlings when buried (14.6 %) compared to those scattered on the soil surface (2.7 %). There was no significant difference in survival between seedlings planted at 2‐3 weeks of age compared with those planted at 12 months of age after 20 months in situ growth. Additionally, those seedlings planted when younger were significantly taller (29.0 ± 2.9 cm) than those that were planted at 12 months of age (4.7 ± 0.3 cm). Use of "onion bag" guards improved survival from 58.1 ± 4.0 % (no guard) to 70.8 ± 3.4 % with an onion bag guard. The use of shade cloth guards did not significantly improve survival, however plant height did increase substantially after 32 months growth (22 cm compared with 7.2 cm for no guard). These data demonstrate that consideration needs to be given to specific species requirements to improve seedling emergence and survival when attempting to return difficult to germinate species to the post‐mining environment.